Gas‐foamed poly(lactide‐co‐glycolide) and poly(lactide‐co‐glycolide) with bioactive glass fibres demonstrate insufficient bone repair in lapine osteochondral defects. (18th February 2019) - Salonius, Eve; Muhonen, Virpi; Lehto, Kalle; Järvinen, Elina; Pyhältö, Tuomo; Hannula, Markus; Aula, Antti S.; Uppstu, Peter; Haaparanta, Anne‐Marie; Rosling, Ari; Kellomäki, Minna; Kiviranta, Ilkka
Abstract: Deep osteochondral defects may leave voids in the subchondral bone, increasing the risk of joint structure collapse. To ensure a stable foundation for the cartilage repair, bone grafts can be used for filling these defects. Poly(lactide‐co‐glycolide) (PLGA) is a biodegradable material that improves bone healing and supports bone matrix deposition. We compared the reparative capacity of two investigative macroporous PLGA‐based biomaterials with two commercially available bone graft substitutes in the bony part of an intra‐articular bone defect created in the lapine femur. New Zealand white rabbits ( n = 40) were randomized into five groups. The defects, 4 mm in diameter and 8 mm deep, were filled with neat PLGA; a composite material combining PLGA and bioactive glass fibres (PLGA–BGf); commercial beta‐tricalcium phosphate (β‐TCP) granules; or commercial bioactive glass (BG) granules. The fifth group was left untreated for spontaneous repair. After three months, the repair tissue was evaluated with X‐ray microtomography and histology. Relative values comparing the operated knee with its contralateral control were calculated. The relative bone volume fraction ( ∆BV/TV ) was largest in the β‐TCP group ( p ≤ 0.012), which also showed the most abundant osteoid. BG resulted in improved bone formation, whereas defects in the PLGA–BGf group were filled with fibrous tissue. Repair with PLGA did not differ from spontaneous repair. The PLGA, PLGA–BGf, and spontaneous groups showed thicker and sparser trabeculae than the commercial controls. We conclude that bone repair with β‐TCP and BG granules was satisfactory, whereas the investigational PLGA‐based materials were only as good as or worse than spontaneous repair.